The association of antiviral drugs with COVID-19 morbidity: The retrospective analysis of a nationwide COVID-19 cohort - Babayigit, Cenk; Kokturk, Nurdan; Kul, Seval; Cetinkaya, Pelin Duru; Nayci, Sibel Atis; Baris, Serap Argun; Bayram, Hasan (Frontiers Media Sa, 2022)
Background and objectivesAlthough several repurposed antiviral drugs have been used for the treatment of COVID-19, only a few such as remdesivir and molnupiravir have shown promising effects. The objectives of our study were to investigate the association of repurposed antiviral drugs with COVID-19 morbidity. MethodsPatients admitted to 26 different hospitals located in 16 different provinces between March 11-July 18, 2020, were enrolled. Case definition was based on WHO criteria. Patients were managed according to the guidelines by Scientific Board of Ministry of Health of Turkey. Primary outcomes were length of hospitalization, intensive care unit (ICU) requirement, and intubation. ResultsWe retrospectively evaluated 1,472 COVID-19 adult patients; 57.1% were men (mean age = 51.9 +/- 17.7years). A total of 210 (14.3%) had severe pneumonia, 115 (7.8%) were admitted to ICUs, and 69 (4.7%) were intubated during hospitalization. The median (interquartile range) of duration of hospitalization, including ICU admission, was 7 (5-12) days. Favipiravir (n = 328), lopinavir/ritonavir (n = 55), and oseltamivir (n = 761) were administered as antiviral agents, and hydroxychloroquine (HCQ, n = 1,382) and azithromycin (n = 738) were used for their immunomodulatory activity. Lopinavir/ritonavir (beta [95% CI]: 4.71 [2.31-7.11]; p = 0.001), favipiravir (beta [95% CI]: 3.55 [2.56-4.55]; p = 0.001) and HCQ (beta [95% CI]: 0.84 [0.02-1.67]; p = 0.046) were associated with increased risk of lengthy hospital stays. Furthermore, favipiravir was associated with increased risks of ICU admission (OR [95% CI]: 3.02 [1.70-5.35]; p = 0.001) and invasive mechanical ventilation requirement (OR [95% CI]: 2.94 [1.28-6.75]; p = 0.011). ConclusionOur findings demonstrated that antiviral drugs including lopinavir, ritonavir, and favipiravir were associated with negative clinical outcomes such as increased risks for lengthy hospital stay, ICU admission, and invasive mechanical ventilation requirement. Therefore, repurposing such agents without proven clinical evidence might not be the best approach for COVID-19 treatment.
Keywords: antiviral agents; COVID-19 morbidity; length of hospitalization; ICU requirement; invasive mechanical ventilation